Hopanoids play a role in stress tolerance and nutrient storage in the cyanobacterium Nostoc punctiforme. Issue 1 (16th August 2016) - Ricci, J. N.; Morton, R.; Kulkarni, G.; Summers, M. L.; Newman, D. K.
Abstract: Hopanes are abundant in ancient sedimentary rocks at discrete intervals in Earth history, yet interpreting their significance in the geologic record is complicated by our incomplete knowledge of what their progenitors, hopanoids, do in modern cells. To date, few studies have addressed the breadth of diversity of physiological functions of these lipids and whether those functions are conserved across the hopanoid‐producing bacterial phyla. Here, we generated mutants in the filamentous cyanobacterium, Nostoc punctiforme, that are unable to make all hopanoids ( shc ) or 2‐methylhopanoids ( hpnP ). While the absence of hopanoids impedes growth of vegetative cells at high temperature, the shc mutant grows faster at low temperature. This finding is consistent with hopanoids acting as membrane rigidifiers, a function shared by other hopanoid‐producing phyla. Apart from impacting fitness under temperature stress, hopanoids are dispensable for vegetative cells under other stress conditions. However, hopanoids are required for stress tolerance in akinetes, a resting survival cell type. While 2‐methylated hopanoids do not appear to contribute to any stress phenotype, total hopanoids and to a lesser extent 2‐methylhopanoids were found to promote the formation of cyanophycin granules in akinetes. Finally, although hopanoids support symbiotic interactions between Alphaproteobacteria and plants, they do not appear to facilitate symbiosis between N. punctiforme and the hornwort Anthoceros punctatus . Collectively, these findings support interpreting hopanes as general environmental stress biomarkers. If hopanoid‐mediated enhancement of nitrogen‐rich storage products turns out to be a conserved phenomenon in other organisms, a better understanding of this relationship may help us parse the enrichment of 2‐methylhopanes in the rock record during episodes of disrupted nutrient cycling.